Democracy, Credibility, and Clientelism - Keefer, Philip; Vlaicu, Razvan (2012)
Despite having adopted the political institutions of established democracies, democratizing countries display a systematically different pattern of fiscal outcomes. This article attributes these differences to the low credibility of electoral promises in new democracies. We study a model of electoral competition where candidates have two costly means to make themselves credible: spending resources to communicate directly with voters and exploiting preexisting patron-client networks. The costs of building credibility are endogenous and lead to higher targeted transfers and corruption and lower public good provision. The analysis demonstrates that in low-credibility states, political appeals to patron-client networks may be welfare enhancing, but in the long run, they delay political development by discouraging direct appeals to voters that are essential for credible mass-based political parties. The model explains why public investment and corruption are higher in younger democracies and why democratizing reforms had greater success in Victorian England than in the Dominican Republic.